A dust-proof and self-cleaning ZnO double-layer white coating for use on the lunar surface and a preparation method thereof
By designing a micro-nano rough structure modified by low-surface energy substances on the surface of the thermally controlled coating, the temperature change problem caused by moon dust adhesion is solved, and the thermal control and dust removal performance is achieved, which is suitable for deep space exploration.
Patent Information
- Application Number
- CN202410684823.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-05-30
AI Technical Summary
During the lunar exploration process, the thermal control coating changes in temperature due to the attachment of lunar dust, which affects the normal operation of the spacecraft. The existing technology is difficult to effectively prevent lunar dust from adhesion, and the material design is relatively simple, so it is impossible to ensure both thermal control and dust removal performance. .
Design a transparent hydrophobic dustproof coating to achieve dust-proof effect while maintaining heat-controlled coating by forming a micro-nano rough structure modified by low-surface energy substances. Control performance.
It achieves stable performance of thermal control coatings in extreme environments, significantly improves dust removal performance, is suitable for deep space exploration, and has excellent thermal control and dust protection effects.
Smart Images

Figure CN118440548B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of special functional materials for space, and relates to a white coating with dustproof and thermal control functions and a preparation method thereof, which can be applied to the field of deep space exploration and has a very broad application prospect. Specifically, it relates to a dustproof and self-cleaning ZnO double-layer white coating applied to the lunar surface and a preparation method thereof. Background Art
[0002] As the focus of current deep space exploration, the moon is a key step for human civilization to move towards the universe. However, there are certain difficulties in the process of lunar exploration. In deep space exploration missions, spacecraft need to withstand extreme space environments. In a vacuum environment, the spacecraft is directly exposed to sunlight, and the surface will produce large temperature changes, causing the internal precision devices to fail. Therefore, the thermal control system is one of the important guarantee systems for the normal operation of spacecraft. The use of thermal control materials is the main way to regulate the thermal control performance of spacecraft. At present, paint-type thermal control coatings have become the most widely used type of thermal control materials in spacecraft due to their advantages of low cost, low implementation difficulty, and high surface universality. However, in the process of exploring the moon, in addition to the extreme temperature environment, due to the effects of cosmic rays, solar wind, and meteor impacts, the surface of the moon is covered with a layer of fine granular weathering materials with an average particle size of about 70μm, called moon dust. The surface of moon dust carries a certain charge and has sharp edges, which is very easy to adhere to the surface of the solid. When moon dust adheres to the thermal control coating, it will greatly affect the thermal control performance of the thermal control coating, causing a large temperature change on the surface of the spacecraft, hindering the progress of the space mission. Therefore, research on protecting thermal control coatings from lunar dust contamination is of far-reaching significance.
[0003] Paint-type thermal control coatings are mainly composed of pigments and binders. The pigments reduce the surface temperature of the coating by reflecting VIS and NIR as well as their own thermal radiation, thus playing a role in thermal control. In paint-type thermal control coatings, the most common pigments are metal oxides or metal salts such as ZnO, ZrO2, and BaSO4; binders are used to bond, fix, and disperse pigments, playing a role in maintaining the stability of the thermal control coating performance. Among pigments, the bandgap width of ZnO is 3.37eV, and the refractive index is as high as about 2, so it is the most widely studied in thermal control coatings. In order to prevent lunar dust from adhering to the surface of thermal control coatings, lunar dust protection technology needs to be applied, which can usually be divided into active protection and passive protection technology. Active technology uses external force to protect the surface from dust deposition, mainly including fluid removal, mechanical removal, and electric field force removal. Fluid removal has a low dust removal efficiency; mechanical dust removal requires manual operation, has a narrow application scenario, and is prone to damage the surface; the device for removing lunar dust by electric field force is relatively complex and there is a risk of mechanical failure. Therefore, the research on passive lunar dust protection technology has become a hot topic in current research. Passive lunar dust protection technology reduces dust adhesion by physically or chemically pre-treating the solid surface. After installation, no external force is used. It has the characteristics of low cost and high reliability. Therefore, it is possible to consider developing a dust-proof self-cleaning ZnO modified white coating to realize the use of thermal control coatings in the lunar environment.
[0004] In the development of dust-proof and self-cleaning thermal control coatings, it is necessary to use surface modification to reduce the adhesion between the dust layer and the protected surface on the basis of the thermal control coating, so as to achieve the effect of surface dust reduction. The adhesion between dust and the surface is divided into three types: van der Waals force, electrostatic force and capillary force. Lunar dust has the characteristics of small particle size and high surface energy. When it comes into contact with the solid surface, it has a huge van der Waals force and exhibits strong adhesion. Space radiation and meteor impact cause the surface of lunar dust to have obvious static charges. Under the action of electrostatic force, it is very easy to adhere to the solid surface. Due to the high vacuum environment on the lunar surface, the role of capillary force can be ignored when studying the passive protection of lunar dust. Considering the numerical values of the three forces of van der Waals force, electrostatic force and capillary force, it is generally only necessary to consider reducing the van der Waals force to achieve dust-proof adhesion on the coating surface. Summary of the invention
[0005] Existing technologies and materials rarely mention methods for maintaining dust-proof adhesion protection on thermal control coatings to achieve stable performance of thermal control coatings. In addition, the material design concept is relatively simple, and there is little research on the development and utilization of new materials.
[0006] Traditional thermal control materials often only consider pigment modification or binder modification, and rarely take improvements in coating design, resulting in limited coating applications. The present invention prepares a transparent hydrophobic dust-proof coating on the basis of the ZnO thermal control coating, thereby realizing the preparation of a thermal control and dust-proof multifunctional coating, thereby achieving stable performance of the thermal control coating under lunar dust pollution.
[0007] In addition, some researchers have studied the synergistic effect of composite materials. For thermal control coatings, there is a contradiction between the thermal control performance and dust removal performance of the coating due to the control of pigment particle size. It is impossible to ensure that the dust removal performance and thermal control performance of the material are achieved at the same time, and there are limitations in application. The present invention designs a double-layer coating, and the top coating adopts a micro-nano rough structure design concept modified by low surface energy materials. While maintaining the thermal control performance of the thermal control coating, the thermal control performance of the coating is retained to the maximum extent, and the synergistic effect of nanoparticles of different particle sizes is fully considered, which greatly improves the dust removal performance of the thermal control coating.
[0008] The present invention uses a special transparent coating on the surface of the thermal control coating. By simultaneously designing the surface structure and surface material of the transparent coating, on the one hand, the contact area between dust particles and the coating surface can be reduced, and because the solid surface energy is low, there will be a lower van der Waals force between the dust and the surface, and compared with a flat surface, the surface will show lower dust adhesion.
[0009] The invention provides a preparation method of a dustproof adhesion self-cleaning ZnO double-layer white coating material applied to the lunar surface. A large-particle ZnO powder (200nm-600nm) material is uniformly mixed with a resin bonding agent to form a white slurry. Finally, the slurry is covered on an alloy substrate by a scraping technique. After curing, a small-particle (20nm-100nm) ZnO powder modified by a low surface energy modifier is dispersed in a mixed solution of ethanol and water. A transparent dustproof coating is formed on the surface of a thermal control coating by a spraying technique, and finally a dustproof adhesion self-cleaning ZnO double-layer white coating is formed.
[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0011] The object of the present invention is to provide a method for preparing a dust-proof and self-cleaning ZnO double-layer white coating for use on the lunar surface, comprising the following steps:
[0012] Step 1, uniformly mixing ZnO pigment with a particle size of 200nm-600nm and an organic binder to obtain a slurry;
[0013] Step 2: Spray the slurry onto the metal substrate using a scraper coating technique, and form a white thermal control coating after curing;
[0014] Step 3: using a vapor deposition method to modify ZnO with a particle size of 20 nm to 100 nm using a low surface energy modifier, and dispersing the modified ZnO in an ethanol / water mixed solution to obtain a dustproof liquid;
[0015] Step 4: spray the dust-proof liquid onto the white thermal control coating using a spraying technique to form the coating.
[0016] It is further defined that the mixing in step 1 is performed using a cutting mixer.
[0017] It is further defined that the stirring rate of the cutting mixer in step 1 is 1000-3000 rpm, such as 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, etc.;
[0018] It is further defined that the stirring time in step 1 is 1-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.
[0019] It is further defined that the organic adhesive in step 1 is epoxy resin, acrylic resin, silicone or polyethylene.
[0020] In step 1, the ZnO particle size can be 200nm, 300nm, 400nm, 500nm, 600nm, etc.;
[0021] It is further defined that in step 1, the color-to-base ratio is 1:(1-5), for example, 1:1, 1:2, 1:3, 1:4, 1:5, etc.
[0022] It is further defined that in step 2, the substrate is an aluminum alloy, a titanium alloy, a magnesium alloy, etc.
[0023] It is further defined that the coating thickness in step 2 is 100 μm-300 μm, for example, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm.
[0024] It is further defined that the curing temperature in step 2 is 60°C-100°C, for example 60°C, 70°C, 80°C, 90°C, 100°C.
[0025] In step 3, the ZnO particle size can be 20nm, 40nm, 60nm, 80nm, 100nm, etc.;
[0026] It is further defined that the deposition time in step 3 is 6 h-48 h, for example 6 h, 12 h, 24 h, 36 h, 48 h.
[0027] It is further defined that the low surface energy modifier in step 3 is hexamethyldisilazane, heptadecafluorodecyltrimethoxysilane or octadecyltriethylsilane.
[0028] It is further defined that the mass ratio of water to anhydrous ethanol is 3:1-1:3, for example, 3:1, 2:1, 1:1, 1:2, 1:3, etc.
[0029] It is further defined that the mass ratio of the modified ZnO particles to the mixed solution of ethanol / water is 1:5-1:25, for example, 1:5, 1:10, 1:15, 1:20, 1:25, etc.
[0030] It is further defined that the spraying distance in step 4 is 10 cm-30 cm, for example, 10 cm, 15 cm, 20 cm, 25 cm, 30 cm, etc.
[0031] It is further defined that the spraying pressure in step 4 is 0.4 MPa-1 MPa, for example, 0.4 MPa, 0.6 MPa, 0.8 MPa, 1 MPa, etc.
[0032] The present invention also provides a dust-proof and self-cleaning ZnO double-layer white coating prepared by any of the above methods for use on the lunar surface.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention designs a multifunctional coating integrating dustproof and thermal control functions for the first time, selects ZnO as the main raw material of the coating, and prepares a layer of transparent hydrophobic dustproof coating on the basis of the ZnO thermal control coating, thereby achieving dustproof adhesion without affecting the thermal control performance of the thermal control coating.
[0035] The present invention adopts a phase separation method. Due to the different volatilization rates of water and ethanol in the dust-proof liquid, the modified ZnO in the dust-proof liquid is driven to assemble, and a micro-nano rough structure is constructed on the surface of the thermal control coating. When the lunar dust contacts the solid surface, the coating surface has a certain rough structure. The micro-convex structure on the surface can reduce the contact area between the dust particles and the coating surface. In addition, since the small-particle ZnO is modified by a low-surface-energy modifier, the solid surface energy is low, and there is a low van der Waals force between the dust and the surface, showing low lunar dust adhesion, thereby achieving the dust-proof performance of the thermal control coating.
[0036] The invention uniformly mixes large-particle ZnO powder material with resin to form a white slurry, and finally covers the slurry on the alloy substrate by scraping technology. After solidification, the small-particle ZnO powder modified by the low surface energy modifier is dispersed in a mixed solution of ethanol and water, and a transparent dustproof coating is formed on the surface of the thermal control coating by spraying technology, and finally a dustproof adhesion self-cleaning ZnO double-layer white coating is formed. The composition and surface morphology of the coating material can be controlled by the process conditions of small-particle ZnO modification, the pigment-to-base ratio of the slurry, the process conditions of ZnO modification and the process conditions of spraying.
[0037] Due to the different particle size control of ZnO, the bottom layer of large-particle ZnO and the top layer of small-particle ZnO work together, so that the white coating has excellent thermal control and dust-proof effects.
[0038] In addition, the white coating has a low solar absorption ratio and high emissivity, stable structural performance under extreme conditions (pressure, temperature, irradiation), and excellent mechanical properties. It is suitable for the actual mission environment of spacecraft and can be used in deep space exploration and other fields.
[0039] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The dustproof test results of the ZnO200-20-A white coating prepared in Example 1 of the present invention;
[0041] Figure 2 The solar spectrum absorption test results of the ZnO200-20-A white coating prepared in Example 1 of the present invention;
[0042] Figure 3 This is the spectral emission test result of the ZnO200-20-A white coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0044] Example 1: ZnO200-20-A coating
[0045] The invention provides a method for preparing a dust-proof adhesion self-cleaning ZnO double-layer white coating. The coating is obtained by spraying a dust-proof liquid on the white coating through a spraying technology.
[0046] 1. The preparation of ZnO white coating is as follows:
[0047] Select 200nm ZnO as the pigment, select acrylic resin as the organic binder, set the pigment-to-base ratio to 1:3, set the speed of the cutting mixer to 2000rpm, stir at room temperature for 2h, select aluminum alloy as the metal substrate, and ultrasonically clean the sandblasted aluminum alloy substrate with acetone and anhydrous ethanol. After the slurry is evenly stirred, it is evenly coated on the aluminum alloy substrate by scraping. The coating thickness is 150μm and cured in an oven at 80℃ for 4h.
[0048] 2. Prepare dust-proof liquid:
[0049] Select 20nm ZnO as the pigment, select hexamethyldisilazane as the low surface energy modifier, vapor deposit for 24h, take out the modified powder, prepare a water / ethanol mixed solution with a mass ratio of 1:1, set the mass ratio of modified ZnO powder to water / ethanol solution to 1:15, add zirconium beads, and stir at room temperature for 4h.
[0050] 3. Spray the dust-proof liquid on the white coating:
[0051] After the white coating is dried, it is placed in the spraying room. The spraying distance is controlled to be 20 cm, the spraying pressure is controlled to be 0.6 MPa, and after 5 cycles of spraying, it is dried in an oven at 80°C for 2 hours to obtain a dust-proof white coating.
[0052] Example 2: ZnO300-20-A coating
[0053] The invention provides a method for preparing a dust-proof adhesion self-cleaning ZnO double-layer white coating. The coating is obtained by spraying a dust-proof liquid on the white coating through a spraying technology.
[0054] 1. The preparation of ZnO white coating is as follows:
[0055] 300nm ZnO was selected as the pigment, acrylic resin was selected as the organic binder, the pigment-to-base ratio was set to 1:4, the speed of the cutting mixer was set to 2000rpm, and stirring was carried out at room temperature for 2h. Aluminum alloy was selected as the metal substrate, and the sandblasted aluminum alloy substrate was ultrasonically cleaned with acetone and anhydrous ethanol. After the slurry was stirred evenly, it was evenly scraped on the aluminum alloy substrate by scraping. The coating thickness was 150μm and cured in an oven at 80℃ for 4h.
[0056] 2. Prepare dust-proof liquid:
[0057] Select 20nm ZnO as the pigment, select hexamethyldisilazane as the low surface energy modifier, vapor deposit for 24h, take out the modified powder, prepare a water / ethanol mixed solution with a mass ratio of 1:1, set the mass ratio of modified ZnO powder to water / ethanol solution to 1:15, add zirconium beads, and stir at room temperature for 4h.
[0058] 3. Spray the dust-proof liquid on the white coating:
[0059] After the white coating is dried, it is placed in the spraying room. The spraying distance is controlled to be 20 cm, the spraying pressure is controlled to be 0.6 MPa, and after 5 cycles of spraying, it is dried in an oven at 80°C for 2 hours to obtain a dust-proof white coating.
[0060] Example 3: ZnO300-20-B coating
[0061] The invention provides a method for preparing a dust-proof adhesion self-cleaning ZnO double-layer white coating. The coating is obtained by spraying a dust-proof liquid on the white coating through a spraying technology.
[0062] 1. The preparation of ZnO white coating is as follows:
[0063] 300nm ZnO was selected as the pigment, acrylic resin was selected as the organic binder, the pigment-to-base ratio was set to 1:4, the speed of the cutting mixer was set to 2000rpm, and stirring was carried out at room temperature for 2h. Aluminum alloy was selected as the metal substrate, and the sandblasted aluminum alloy substrate was ultrasonically cleaned with acetone and anhydrous ethanol. After the slurry was stirred evenly, it was evenly scraped on the aluminum alloy substrate by scraping. The coating thickness was 150μm and cured in an oven at 80℃ for 4h.
[0064] 2. Prepare dust-proof liquid:
[0065] Select 20nm ZnO as the pigment, select heptadecafluorodecyltrimethoxysilane as the low surface energy modifier, vapor deposit for 48h, take out the modified powder, prepare a water / ethanol mixed solution with a mass ratio of 1:2, set the mass ratio of modified ZnO powder to water / ethanol solution to 1:15, add zirconium beads, and stir at room temperature for 4h.
[0066] 3. Spray the dust-proof liquid on the white coating:
[0067] After the white coating is dried, it is placed in the spraying room. The spraying distance is controlled to be 20 cm, the spraying pressure is controlled to be 0.6 MPa, and after 5 cycles of spraying, it is dried in an oven at 80°C for 2 hours to obtain a dust-proof white coating.
[0068] Example 4: ZnO200-60-A coating
[0069] The invention provides a method for preparing a dust-proof adhesion self-cleaning ZnO double-layer white coating. The coating is obtained by spraying a dust-proof liquid on the white coating through a spraying technology.
[0070] 1. The preparation of ZnO white coating is as follows:
[0071] Select 200nm ZnO as the pigment, select acrylic resin as the organic binder, set the pigment-to-base ratio to 1:3, set the speed of the cutting mixer to 2000rpm, stir at room temperature for 2h, select aluminum alloy as the metal substrate, and ultrasonically clean the sandblasted aluminum alloy substrate with acetone and anhydrous ethanol. After the slurry is evenly stirred, it is evenly coated on the aluminum alloy substrate by scraping. The coating thickness is 150μm and cured in an oven at 80℃ for 4h.
[0072] 2. Prepare dust-proof liquid:
[0073] Select 60nm ZnO as the pigment, select heptadecafluorodecyltrimethoxysilane as the low surface energy modifier, vapor deposit for 48h, take out the modified powder, prepare a water / ethanol mixed solution with a mass ratio of 1:1, set the mass ratio of modified ZnO powder to water / ethanol solution to 1:15, add zirconium beads, and stir at room temperature for 4h.
[0074] 3. Spray the dust-proof liquid on the white coating:
[0075] After the white coating is dried, it is placed in the spraying room. The spraying distance is controlled to be 20 cm, the spraying pressure is controlled to be 0.6 MPa, and after 5 cycles of spraying, it is dried in an oven at 80°C for 2 hours to obtain a dust-proof white coating.
[0076] For the coating prepared in the above embodiment, we conducted the following tests:
[0077] Dust removal performance test: We used ZnO200-20-A coating to conduct dust removal test. During the test, we first sprinkled dust evenly on the sample surface, then fixed the dusty sample on the platform surface and moved it slowly until the dust slid off, and recorded the tilt angle when it slid off. The test results show that ZnO200-20-A coating has a lower dust removal angle, proving that ZnO200-20-A coating has excellent lunar dust protection performance.
[0078] Solar spectrum absorption test: We used the ZnO200-20-A coating prepared in Example 1 to test the absorption of sunlight. The test showed that the ZnO200-20-A coating has good reflective performance in the solar spectrum band, with an average absorption rate of 14.42, which has reached the reflective performance of commercial coatings in the solar spectrum band.
[0079] Infrared emission measurement: We used the ZnO200-20-A coating prepared in Example 1 to test the absorption of sunlight. The test showed that the ZnO200-20-A coating had good spectral emission performance with an average reflectivity of 86.09, which has reached the infrared emission performance of commercial coatings.
[0080] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.
Claims
1. A method for preparing a dust-proof and self-cleaning ZnO double-layer white coating for use on the lunar surface, characterized in that: The following steps are involved: Step 1, uniformly mixing ZnO pigment with a particle size of 200nm-600nm and an organic binder to obtain a slurry; Step 2: Use a scraping technique to scrape the slurry onto a metal substrate, and after curing, form a white thermal control coating; Step 3: using a vapor deposition method to modify ZnO with a particle size of 20 nm to 60 nm using a low surface energy modifier, and dispersing the modified ZnO in an ethanol aqueous solution to obtain a dustproof liquid; Step 4: spraying the dustproof liquid on the white thermal control coating using a spraying technique to form the coating; Among them, the deposition time is 6h-48h; The low surface energy modifier is hexamethyldisilazane, heptadecafluorodecyltrimethoxysilane or octadecyltriethylsilane; the mass ratio of water to anhydrous ethanol is 3:1-1:3; the mass ratio of modified ZnO particles to ethanol aqueous solution is 1:(5-25); The spraying distance is 10cm-30cm, and the spraying pressure is 0.4MPa-1MPa.
2. The method according to claim 1, characterized in that: The organic adhesive is epoxy resin, acrylic resin, silicone or polyethylene.
3. The method according to claim 1, characterized in that: Color to base ratio 1: (1-5).
4. The method according to claim 1, characterized in that: The substrate is aluminum alloy, titanium alloy, and magnesium alloy.
5. The method according to claim 1, characterized in that: The coating thickness is 100μm-300μm.
6. The method according to claim 1, characterized in that: The curing temperature is 60℃-100℃.
7. A dust-proof and self-cleaning ZnO double-layer white coating for use on the lunar surface, prepared by the method according to any one of claims 1 to 6.
